2020
DOI: 10.18632/aging.102605
|View full text |Cite
|
Sign up to set email alerts
|

PRDX5 as a novel binding partner in Nrf2-mediated NSCLC progression under oxidative stress

Abstract: Non-small-cell lung cancer (NSCLC) is one of the most common malignant tumors in the world. Reactive oxidative species (ROS) and nuclear factor-related factor 2 (Nrf2) -antioxidant response element (ARE) signal pathway are known to play important roles in the development of NSCLC. In this study, we identified Peroxiredoxin 5 (PRDX5) as a novel binding partner for Nrf2. PRDX5 was significantly increased in human NSCLC specimens and cell lines. Nrf2 interacted with PRDX5 in H2O2-stimulated NCSLC cells, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Under oxidative stress after gamma irradiation, Keap1 is inactivated, Nrf2 is stabilized, translocated into the nucleus, where it binds to antioxidant response elements (ARE) and initiates transcription of many antioxidative genes, including NQO1. 57 NQO1 is a cytosolic obligatory 2-electron quinone reductase in mammalian systems. It is highly inducible and plays multiple functions in cellular adaptation to oxidative stress.…”
Section: Evaluation Of Free Radical Scavenging Activitymentioning
confidence: 99%
“…Under oxidative stress after gamma irradiation, Keap1 is inactivated, Nrf2 is stabilized, translocated into the nucleus, where it binds to antioxidant response elements (ARE) and initiates transcription of many antioxidative genes, including NQO1. 57 NQO1 is a cytosolic obligatory 2-electron quinone reductase in mammalian systems. It is highly inducible and plays multiple functions in cellular adaptation to oxidative stress.…”
Section: Evaluation Of Free Radical Scavenging Activitymentioning
confidence: 99%
“…PRDX5 is a binding partner of NRF-2 that can promote its activation to induce the expression of a group of functionally diverse cytoprotective factors such as heme oxygenase-1 (HO1) to attenuate inflammation. 46 , 47 However, SHK did not alter the protein levels of NRF-2 and HO1, and the translocation of NRF-2 into the nucleus (Supplementary Fig. 6a–c ), which indicated that PRDX5 was not a target protein of SHK.…”
Section: Resultsmentioning
confidence: 92%
“…Prx5, also called PrxV/AOEB166/PMP20/PLP/ACR1, was discovered twenty years ago and is widely expressed in mammalian tissues [ 20 ]. As an important member of the Prxs family, Prx5 plays a central role in redox signal transduction and exhibits high scavenging activity toward oxidative stress [ 16 ] [ 21 ].…”
Section: Discussionmentioning
confidence: 99%